2021
DOI: 10.3389/fcvm.2021.789669
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma Vitamin B6 With Coronary Heart Disease in Patients Undergoing Diagnostic Coronary Angiography: New Insight on Sex Differences

Abstract: Aim: To date, findings on the overall and sex-specific effects of plasma pyridoxal 5′-phosphate (PLP, active coenzyme form of vitamin B6) on the risk of coronary heart disease (CHD) have been inconsistent. This study sought to advance our understanding on the association of plasma PLP with risk of CHD, with particular attention paid to sex differences and effect modifiers.Methods: We conducted a hospital-based, case-control study on suspected CHD patients undergoing diagnostic coronary angiography. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Previous studies have reported significant associations between low vitamin B6 levels and increased risk of coronary heart disease. More specifically, a significant inverse linear relation of plasma pyridoxal 5'phosphate (the active coenzyme form of vitamin B6) levels and risk of coronary heart disease in women has been reported 34 . However, it should be emphasized that the decreased abundance of this pathway in the STEMI group is for the microbial metabolic pathway not the human pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported significant associations between low vitamin B6 levels and increased risk of coronary heart disease. More specifically, a significant inverse linear relation of plasma pyridoxal 5'phosphate (the active coenzyme form of vitamin B6) levels and risk of coronary heart disease in women has been reported 34 . However, it should be emphasized that the decreased abundance of this pathway in the STEMI group is for the microbial metabolic pathway not the human pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed definitions of the six risk factors for stroke mentioned above are as follows: x hypertension, indicated by a history of high blood pressure with a measurement of ≥140/90 mmHg as reported by the individual or diagnosed by a physician (14); ydiabetes, indicated by fasting plasma glucose levels of ≥7.0 mmol/L or taking glucose-lowering drugs (15); z dyslipidaemia, deemed either self-reported physiciandiagnosed hyperlipidaemia or the use of lipid-lowering drugs (16); {stroke history, characterized by the sudden onset of focal neurologic deficits and diagnosed as either ischemic or haemorrhagic stroke; and |smoking history, defined as smoking at least 1 cigarette per day for >6 months before admission (17); and }drinking history, defined as consuming more than 100 ml of spirit alcohol more than three times a week based on self-report (18). Furthermore, accompanying symptoms and laboratory test results were also recorded.…”
Section: Baseline Characteristics and Data Collectionmentioning
confidence: 99%